The relationship between the Chinese ‘going out’ strategy and international trade - Abeliansky Ana Lucia; Martínez-Zarzoso Inmaculada (Economics: Journal Articles, 2019)
This study is the first to estimate a system of simultaneous gravity equations for Chinese exports, imports and foreign direct investment (FDI) using a sample of 167 countries over the period 2003–2012. The main results indicate that trade and outward FDI are complementary. In particular, the authors show that outward Chinese FDI is related to higher exports and imports and that China trades more with countries hosting Chinese FDI. Results are also robust to the use of instrumental variables. Therefore, Chinese investment seems to foster trade.